Designing of Tuktuk Siadong Lakeside Resort (Tropical Architecture) - Reza Bahrian; Wahyu Utami (Talenta Publisher, 2019)
Lodging in the form of resort hotels are needed in tourist areas such as Lake Toba, to provide a place to rest as well as recreational areas, Tuktuk Siadong Village is one of the villages in Simanindo District which has many recreational areas. The design of resort hotels in the area of Lake Toba must consider the characteristics of traditional buildings around, responsive to tourism potential, and responsive to the climate. These considerations are used to create a resort hotel that has it has characteristics and attracts tourists to visit and stay overnight. The method used in this design is the glass box method by collecting data related to design. The data obtained is then analyzed to find the right hotel resort concept for the design area, namely the concept of Tropical Architecture. They are designing resort hotels in this area as a form of support for government programs in advancing Lake Toba Tourism and advancing the regional economic sector.